CLIMATE CHANGE - CAUSES, CONSEQUENCES AND POSSIBLE SOLUTIONS - Rayhon Rustamova Khorezm region, Yangariq district, School number 5 (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
In this article there is information about why climate change is happening and what can happen because of this problem. Also what can we do for overcoming this issue. Key words: climate change, CO2, methane, fossil fuels, sea levels, underwater cities, human activities, warmer periods, greenhouse gases